The Roles of Kidney-Resident ILC2 in Renal Inflammation and Fibrosis - Nagashima, Ryuichi; Iyoda, Masayuki (Frontiers in Immunology, 2021)
Innate lymphoid cells (ILCs) are a recently discovered lymphocyte population with high cytokine productive capacity. Type-2 ILCs (ILC2s) are the most studied, and they exert a rapid type-2 immune response to eliminate helminth infections. Massive and sustainable ILC2 activation induces allergic tissue inflammation, so it is important to maintain correct ILC2 activity for immune homeostasis. The ILC2-activating cytokine IL-33 is released from epithelial cells upon tissue damage, and it is upregulated in various kidney disease mouse models and in kidney disease patients. Various kidney diseases eventually lead to renal fibrosis, which is a common pathway leading to end-stage renal disease and is a chronic kidney disease symptom. The progression of renal fibrosis is affected by the innate immune system, including renal-resident ILC2s; however, the roles of ILC2s in renal fibrosis are not well understood. In this review, we summarize renal ILC2 function and characterization in various kidney diseases and highlight the known and potential contributions of ILC2s to kidney fibrosis.